Transvenous interventional implantation of CRT‐D in a critically ill Mustard patient waiting for heart transplant. Issue 7 (14th June 2019) - Mörtsell, David; Thilén, Ulf; Tydén, Patrik; Kongstad, Ole
Abstract: Cardiac resynchronization therapy may stabilize patients with severe heart failure awaiting heart transplant. Transvenous interventional implantation aided by intracardiac echocardiography is feasible in patients with adult congenital heart disease. Abstract : Cardiac resynchronization therapy may stabilize patients with severe heart failure awaiting heart transplant. Transvenous interventional implantation aided by intracardiac echocardiography is feasible in patients with adult congenital heart disease.